Changes in plasma levels of B-type natriuretic peptide with acute exacerbations of chronic obstructive pulmonary disease - Nishimura, Koichi (Dove Medical Press, 2014)
BACKGROUND: Elevated plasma B-type natriuretic peptide (BNP) levels and their association with heart failure have been reported in subjects with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). PURPOSE: To examine and compare plasma BNP levels and diastolic and systolic dysfunction in subjects with AECOPD and stable chronic obstructive pulmonary disease (COPD). METHODS: In all, 87 unselected consecutive hospitalizations due to AECOPD in 61 subjects and a total of 190 consecutive subjects with stable COPD were recruited. Plasma BNP levels were compared cross-sectionally and longitudinally. Transthoracic echocardiographic examinations were also performed in the hospitalized subjects. RESULTS: In the hospitalized subjects, the median plasma BNP level (interquartile range) was 55.4 (26.9–129.3) pg/mL and was higher than that of patients with stable COPD: 18.3 (10.0–45.3) for Global Initiative for Chronic Obstructive Lung Disease grade I; 25.8 (11.0–53.7) for grade II; 22.1 (9.1–52.6) for grade III; and 17.2 (9.6–22.9) pg/mL for grade I V, all P<0.001. In 15 subjects studied prospectively, the median plasma BNP level was 19.4 (9.8–32.2) pg/mL before AECOPD, 72.7 (27.7–146.3) pg/mL during AECOPD, and 14.6 (12.9–39.0) pg/mL after AECOPD (P<0.0033 and P<0.0013, respectively). Median plasma BNP levels during AECOPD were significantly higher in ten unsuccessfully discharged subjects 260.5 (59.4–555.0) than in 48 successfully discharged subjects 48.5 (24.2–104.0) pg/mL (P=0.0066). Only 5.6% of AECOPD subjects were associated with systolic dysfunction defined as a left ventricular ejection fraction (LVEF) <50%; a further 7.4% were considered to have impaired relaxation defined as an E/A wave velocity ratio <0.8 and a deceleration time of E >240 ms. BNP levels were weakly correlated with the E/peak early diastolic velocity of the mitral annulus (Ea) ratio (Spearman’s rank correlation coefficient =0.353, P=0.018), but they were not correlated with the LVEF (Spearman’s rank correlation coefficient =−0.221, P=0.108). CONCLUSION: A modest elevation of plasma BNP is observed during AECOPD. It appears that AECOPD may have an impact on plasma BNP levels that is not attributable to heart failure.